Pathways to policy impact: a new approach for planning and evidencing research impact. (31st August 2018) - Reed, Mark S.; Bryce, Rosalind; Machen, Ruth
Abstract : Background The use of research in policy settings is complex, unpredictable and influenced by a range of poorly understood social factors. This makes it difficult to plan for, facilitate and evaluate policy impacts arising from research. Aims and objectives 1. Propose and test tools for planning for and facilitating research impact, based on a new logic model combined with a novel approach to public/stakeholder analysis. 2. Propose and test methods for establishing causal links between research and policy impacts. 3. Use case study findings to provide new empirical insights into the social processes that mediate the generation of impact from research. Methods Social Network Analysis, qualitative analysis of semi-structured interviews, and analysis of secondary data were used in a case study of peatland climate change research in Scottish Government policy. Findings Boundary organisations and centrally-positioned, well-trusted individuals, were crucial to the development of a trusted body of research in which policymakers were sufficiently confident as the basis for policy. Discussion and conclusions The non-linear social dynamics that characterise science-policy networks can be understood and evaluated. By using the tools described in this paper, researchers and other stakeholders can better plan, facilitate and evaluate research impact.